Analysing the mediating effects of job satisfaction and dissatisfaction on employee voluntary turnover intention - Taslima Jannat,; Nor Asiah Omar,; Muhamad Azrin Nazri, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study examines the relationship between performance-based rewards (PR) and training and development (T&D) in terms of employee voluntary turnover intention (TI). It also examines if job satisfaction (JS) and job dissatisfaction (JDS) mediate the relationship between these variables. The data were collected via purposive sampling and were analyzed using the structural equation modelling partial least squares (SEM-PLS method). A total of 409 respondents from private organizations participated in this study. The results reveal that PR and T&D have a significant relationship with TI. This study found that JS mediates the relationship between PR, T&D, and TI while JDS mediates only the relationship between T&D and TI. These findings provide more in-depth insights that can help employers address the turnover intention at workplaces.